PEMANFAATAN LIMBAH BATANG JAGUNG SEBAGAI ADSORBEN ALTERNATIF PADA PENGURANGAN KADAR KLORIN DALAM AIR OLAHAN (TREATED WATER) - Fatimah Hutasuhut, Siswarni MZ (Universitas Sumatera Utara, 2013)
Various result of agricultural waste that contain high cellulose can be used as an alternative adsorbent. One of them was derived from dried corn stalks which traditionally burnt after harvest that lead to environmental pollution. It is necessary to produce the value-added materials from corn stalks waste as an alternative adsorbent to reduce the level of chlorine in treated water. This process was performed by using various level of sulfuric acid concentration 1%, 3% and 5%, particles size 50 and 70 mesh in 105 oC with adsorbtion time 30, 60 and 90 minutes. The most favorable activation result was obtained at 5% concentration, with particle size 70 mesh, adsorbtion time 90 minutes and the iodine value was 482 mg/l with level of adsorbed chlorine was 96,08%. Based on this findings, we concluded that the corn stalks waste can be used as an alternative adsorbent in reducing the level of chlorine in treated water. Keywords: alternative adsorbents, corn stalks, chemical activation